Synthesis of ferrocenyl-substituted 1,3-dithiolanes via [3 + 2]-cycloadditions of ferrocenyl hetaryl thioketones with thiocarbonyl S-methanides - Grzegorz Mlostoń; Róża Hamera-Fałdyga; Anthony Linden; Heinz Heimgartner (Beilstein Journal of Organic Chemistry, 2016)
Ferrocenyl hetaryl thioketones react smoothly with in situ generated thiocarbonyl S-methanides to give 1,3-dithiolanes. In the case of aromatic S-methanides, the sterically more crowded 4,4,5,5-tetrasubstituted 1,3-dithiolanes (2-CH2 isomers) were formed as sole products. The reactions with cycloaliphatic S-methanides led to mixtures of 2-CH2 and 5-CH2 isomers with the major component being the sterically more crowded 2-CH2 isomers. The preferred formation of the latter products is explained by the assumption that the formal [3 + 2]-cycloadducts were formed via a stepwise reaction mechanism with a stabilized 1,5-diradical as a key intermediate. The complete change of the reaction mechanism toward the concerted [3 + 2]-cycloaddition was observed in the reaction of a sterically crowded cycloaliphatic thiocarbonyl ylide with ferrocenyl methyl thioketone.